Pentraxin 3 regulates synaptic function by inducing AMPA receptor clustering via ECM remodeling and β1‐integrin. (5th November 2018) - Fossati, Giuliana; Pozzi, Davide; Canzi, Alice; Mirabella, Filippo; Valentino, Sonia; Morini, Raffaella; Ghirardini, Elsa; Filipello, Fabia; Moretti, Milena; Gotti, Cecilia; Annis, Douglas S; Mosher, Deane F; et al.
Abstract: Control of synapse number and function in the developing central nervous system is critical to the formation of neural circuits. Astrocytes play a key role in this process by releasing factors that promote the formation of excitatory synapses. Astrocyte‐secreted thrombospondins (TSPs) induce the formation of structural synapses, which however remain post‐synaptically silent, suggesting that completion of early synaptogenesis may require a two‐step mechanism. Here, we show that the humoral innate immune molecule Pentraxin 3 (PTX3) is expressed in the developing rodent brain. PTX3 plays a key role in promoting functionally‐active CNS synapses, by increasing the surface levels and synaptic clustering of AMPA glutamate receptors. This process involves tumor necrosis factor‐induced protein 6 (TSG6), remodeling of the perineuronal network, and a β1‐integrin/ERK pathway. Furthermore, PTX3 activity is regulated by TSP1, which directly interacts with the N‐terminal region of PTX3. These data unveil a fundamental role of PTX3 in promoting the first wave of synaptogenesis, and show that interplay of TSP1 and PTX3 sets the proper balance between synaptic growth and synapse function in the developing brain. Synopsis: Pentraxin 3 (PTX3) is a soluble innate immunity molecule that plays a key role in recognition and binding of microbial moieties and complement components. PTX3 also interacts with extracellular matrix components and contributes to the structural three‐dimensional organization of the extracellular matrix. PTX3 is expressed and released by glial cells in the developing rodent brain. PTX3 promotes formation and maturation of excitatory synapses by enhancing the synaptic recruitment of AMPARs. PTX3 regulates synaptic AMPARs through the remodeling of ECM surrounding excitatory synapses. Glial‐derived thrombospondin‐1 (TSP1) regulates PTX3 activity through direct interaction. Abstract : Murine astrocytes release innate immunity‐associated PTX3 at early postnatal stages, where it plays a key role in the functional maturation of excitatory synapses by promoting AMPAR recruitment at synapses.